(untitled) (Journal of Biochemistry, Microbiology and Biotechnology, 2020)
Microbial heavy metals reduction has an important role in the biological system and in environmental metals recycling to remove its toxic effects in soil and wastewater. A molybdenum-reducing bacterium with the potential to reduce toxic hexavalent molybdenum to colloidal molybdenum blue (Mo-blue) was isolated from agricultural land in Northwest-Nigeria. The Gram’s stain and microscopic examination reveal that the isolate is a Gram-negative, however, phylogenetic analysis of the 16S rRNA identifies the isolate as Pseudomonas sp. Molybdenum reduction in this bacterium is optimally supported by glucose at 1.0% (w/v). The optimum phosphate and molybdate concentrations supporting molybdate reduction were between 3.5 and 7.5 mM for phosphate and 100 mM molybdate. Molybdate reduction is optimum at 37 ᵒC and pH between 6.5 and 7.5. The capacity of this isolate to reduce toxic molybdenum to a less toxic form is novel and makes the bacterium an important instrument for bioremediation of this pollutant.